Analysis Of The Negative Technogenic And Environmental Impact On The Architectural Monuments Of Khiva (The Peerian Journal, 2025)
he Ichan Kala architectural complex in Khiva, considered a pearl of traditional architecture, was recognized in 1967 as the only city-reserve in Central Asia. In December 1990, it was designated a UNESCO World Heritage Site. The city was granted the official status of "Open-Air Museum City." Khiva and Bukhara, "of global significance, require protection from the influence of time and human intervention." The inclusion of the architectural monuments of Khiva and Bukhara in the list of universal human values confirms their recognition on a global scale. At this time, a careful attitude toward them is a call to each of us"